Extended High-Gain Observer for Mars Entry Guidance - Kai Wu; Hutao Cui; Pingyuan Cui (Institute of Advanced Engineering and Science, 2013)
To deliver a Mars entry vehicle to the prescribed parachute deployment point, active entry guidance is essential. This paper addresses the problem of Mars atmospheric entry guidance through drag tracking method with extended high gain observer. First, an extended high gain observer combined with feedback linearization is applied in drag tracking for Mars entry longitudinal guidance. The observer estimates the drag and drag rate for drag tracking, estimates the perturbation due to model uncertainty and disturbance, and compensate for the perturbation by canceling its estimate. Then, bank reversal is adopted in the lateral plane to reduce the cross-range error. Finally, Mars entry simulation is performed to assess the performance of the adaptive guidance law. The results demonstrate that the proposed guidance law exhibits good performance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1998